Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section - Mcknight, Tristan A.; Cannings, Robert A. (Zootaxa, 2020)
Nearctic species of Lasiopogon Loew comprising the bivittatus section (the bivittatus group sensu Cannings 2002) are revised, with the description of 13 new species, elevation of one subspecies to species, and redescriptions of 13 previously described taxa. An updated key to western Nearctic Lasiopogon adults is provided, as are notes on taxonomy, distribution, phylogeny, and ecology. A Bayesian species tree for 67 species of Lasiopogon is estimated from one mitochondrial (COI) and three nuclear protein-coding loci (AATS, PEPCK, Wg), and compared to a previously published morphology-based phylogeny. The following new species of Lasiopogon are described (assigned to the bivittatus section except as noted): L. anaphlecter sp. nov., L. apoecus sp. nov., L. asilomar sp. nov., L. bitumineus sp. nov., L. canningsi sp. nov., L. condylophorus sp. nov., L. esau sp. nov., L. karli sp. nov. (assigned to cinereus group of opaculus section), L. nelsoni sp. nov., L. odontotus sp. nov., L. sierra sp. nov., L. tumulicola sp. nov., L. wilcoxi sp. nov.; L. puyallupi Cole & Wilcox 1938 stat. nov. is elevated from subspecies; and the following previously described species are considered valid: L. actius Melander 1923, L. albidus Cole & Wilcox 1938, L. arenicola (Osten Sacken 1877), L. bivittatus Loew 1866, L. californicus Cole & Wilcox 1938, L. dimicki Cole & Wilcox 1938, L. drabicolum Cole 1916, L. gabrieli Cole & Wilcox 1938, L. littoris Cole 1924, L. ripicola Melander 1923, L. willametti Cole & Wilcox 1938, L. zonatus Cole & Wilcox 1938. The species L. martinensis Cole & Wilcox 1938 is considered valid but transferred to the tetragrammus group of the opaculus section.